Bridging the Gap Between AI and Reality c - Steffen, Bernhard; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2026)
This open access book constitutes revised selected papers from the Second International Conference on Bridging the Gap between AI and Reality, AISoLA 2024, which took place in Crete, Greece, in October/November 2024. The papers included in this book extend the presentation in the AISoLA 2024 on-site proceedings. They focus on the following topics: AI-Assisted Programming; health care approaches using formal methods and AI; responsible and trusted AI: an interdisciplinary perspective; statistical model checking; and verification for neur-symbolic artificial intelligence. .
Correct-ish by Design: From Upfront Verification to Continuous Monitoring of LLM Generated Code -- Context Engineering for AI-Assisted Programming for Domain-Specific Languages -- The Impact of Generative Artificial Intelligence Tools in Project-Based Learning -- Health Care - Approaches Using Formal Methods and AI -- Towards Person-Owned and Controlled Personal Health Records: Past, Present, and Future Research at eMedLab, TalTech -- LC/NC Pipeline for Training and Operationalising Segmentation Models in a Data Scarce Domain: De-arraying Tissue MicroArrays -- Quantum Machine Learning in Precision Medicine and Drug Discovery - A Game Changer for Tailored Treatments? -- What Computing Professionals Should Know About Ethics: Perspectives of Philosophers -- Disentangling AI Alignment: A Structured Taxonomy Beyond Safety and Ethics -- Epistemic Deference to AI -- Responsibility Attribution for AI-mediated Damages with Mechanistic Interpretability -- Development and Maintenance of Trust in Human-Drone-Interaction: Preliminary empirical findings in a warehouse setting -- Feedback from AI Team Members: Implications on Self-Image and Trust -- Using Statistical Model Checker for Schedulability Analysis of Real-Time Systems under Uncertainty -- A Parametric Model for Near-Optimal Online Synthesis with Robust Reach-Avoid Guarantees.
Accessibility summary: This PDF has been created in accordance with the PDF/UA-1 standard to enhance accessibility, including screen reader support, described non-text content (images, graphs), bookmarks for easy navigation, keyboard-friendly links and forms and searchable, selectable text. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com. Please note that a more accessible version of this eBook is available as ePub.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Computer science; Software engineering; Computers, Special purpose; Computer systems; Artificial intelligence; Computer Science Logic and Foundations of Programming; Software Engineering; Special Purpose and Application-Based Systems; Computer System Implementation; Artificial Intelligence